Immunogenicity and safety of a novel MMR vaccine (live, freeze-dried) containing the Edmonston-Zagreb measles strain, the Hoshino mumps strain, and the RA 27/3 rubella strain: Results of a randomized, comparative, active controlled phase III clinical trial - Ashwani Sood; Monjori Mitra; Himanshu Arvind Joshi; Uma Siddhartha Nayak; Prashanth Siddaiah; T. Ramesh Babu; Samarendra Mahapatro; Jayesh Sanmukhani; Gaurav Gupta; Ravindra Mittal; Reinhard Glueck (Taylor & Francis Group, 2017)
This phase III clinical trial was conducted to evaluate the immunogenicity and safety of the single-dose and multi-dose formulations of a novel MMR vaccine (live, freeze-dried) developed by M/s Cadila Healthcare Limited, India (Cadila MMR vaccine), containing the Hoshino mumps strain, compared to that of an existing MMR vaccine (live, freeze-dried) developed by M/s Serum Institute of India Limited, India (Serum MMR vaccine). These two vaccines have similar measles and rubella strains, but different mumps strains (Hoshino in Cadila MMR vaccine, and L-Zagreb in Serum MMR vaccine). Three hundred and twenty-eight subjects of either sex, aged 15-18 months, were randomized in a 2:1 ratio to receive either the Cadila or Serum MMR vaccine. Immunogenicity assessments (IgG antibodies against measles, mumps, and rubella viruses) were done at baseline and 42 d after vaccination. Solicited (local and systemic) and unsolicited adverse events were recorded for up to 42 d following vaccination. The Cadila MMR vaccine was found to be non-inferior to the Serum MMR vaccine in terms of end-of-study proportion of subjects seropositive for anti-measles antibodies (100.0% in both groups), anti-mumps antibodies (94.5% vs. 94.0%), and anti-rubella antibodies (95.5% vs. 91.0%). Both vaccines were well tolerated by all study participants; the most common adverse event reported in both groups was fever, followed by rash. The results of this phase III clinical trial show that the novel Cadila MMR vaccine is non-inferior to the Serum MMR vaccine.